Volume 1B: 36th Computers and Information in Engineering Conference 2016
DOI: 10.1115/detc2016-60483
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Cyber-Physical Manufacturing Cloud Using MTConnect

Abstract: Cyber-physical systems are gaining momentum in the domain of manufacturing. Cloud Manufacturing is also revolutionizing the manufacturing world. However, although there exist numerous physical manufacturing machines which are network-ready, very few of them are operated in a networked environment due to lack of scalability of existing cyber-physical systems. Combining the features offered by cloud manufacturing and cyber-physical systems, we develop a service-oriented architecture of scalable cyber-physical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The combination of private database and public database indicates the trend of the cloud-based distributed data storage and computing (Ding et al 2018). Besides, the protocols for smart object access such as MTConnect (Liu et al 2016), AutomationML (Schroeder et al 2016) and OPC UA need to be configured.…”
Section: Network Connectivity Configurationmentioning
confidence: 99%
“…The combination of private database and public database indicates the trend of the cloud-based distributed data storage and computing (Ding et al 2018). Besides, the protocols for smart object access such as MTConnect (Liu et al 2016), AutomationML (Schroeder et al 2016) and OPC UA need to be configured.…”
Section: Network Connectivity Configurationmentioning
confidence: 99%
“…MTConnect-based system monitoring is also used for retrieving in-process parts data to quickly generate machining quality reports [30]. Previous research also demonstrated a much wider application of MTConnect towards smart manufacturing, such as sustainable machining [31], machining simulation [32], cloud manufacturing [33], intelligent maintenance [34], and cyber-physical machine tools [35].…”
Section: • Mtconnectmentioning
confidence: 99%
“…16 MTConnect and OPC-Unified Architecture (OPC-UA) are two communication protocols specifically designed for industrial automation. 17,18 MTConnect has been designed towards the Computer Numerical Control (CNC) machine shop with predefined data structures and rules whereas OPC-UA provides a more open user-defined variable structure which results in a wider scope of implementation. 19 OPC-UA has the capability to both receive and send information where MTConnect can only monitor.…”
Section: Introductionmentioning
confidence: 99%